1990
DOI: 10.1111/j.1365-2125.1990.tb03662.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and radionuclide effects of amlodipine in coronary artery disease.

Abstract: 1 The haemodynamic and radionuclide effects of a new long-acting slow-calcium channel blocking agent, amlodipine, were evaluated in 32 patients with coronary artery disease. 2 Haemodynamic measurements in 24 patients were made at rest and 10 to 15 min after 20 mg i.v. amlodipine. Amlodipine significantly reduced systemic arterial blood pressure and vascular resistance index with an increased heart rate and augmented cardiac index. Cardiac stroke volume index rose and stroke work fell without change in pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Present study also showed that there was no significant change (Table 3) When %FS was used as an index to evaluate LV systolic pump function, there were no significant changes in %FS during treatment with Cilnidipine [43], Cilnidipine treatment has no effect on EF and eFS [56], the left ventricular ejection fraction was unaltered after Amlodipine either at rest or during exercise [57,58] and Amlodipine did not affect LVEF at rest or during exercise [59], are corroborative with present study.…”
Section: Discussionmentioning
confidence: 85%
“…Present study also showed that there was no significant change (Table 3) When %FS was used as an index to evaluate LV systolic pump function, there were no significant changes in %FS during treatment with Cilnidipine [43], Cilnidipine treatment has no effect on EF and eFS [56], the left ventricular ejection fraction was unaltered after Amlodipine either at rest or during exercise [57,58] and Amlodipine did not affect LVEF at rest or during exercise [59], are corroborative with present study.…”
Section: Discussionmentioning
confidence: 85%
“… 4 , 6 This is most likely due to direct arterial vasodilatation with improved coronary flow and systemic after-load reduction. 12 , 13 There is increasing interest, however, in targeting further the dysfunctional vascular biology of atherosclerosis, as this may underlie both the disturbances of coronary blood flow in myocardial ischaemia and more serious adverse clinical outcomes. 14 , 15 Statins show a variety of vascular effects in addition to LDL-C lowering, but the clinical relevance of these ‘pleiotropic’ actions has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Verapamil and diltiazem have negative inotropic effects and caution should be exercised when treating patients with signs of congestive heart failure. Amlodipine may also possess a certain negative inotropic effect in patients with angina pectoris, when the recommended treatment dose is exaggerated . In doses of 5–10 mg day −1 amlodipine has not shown any cardiodepressant effect .…”
Section: Discussionmentioning
confidence: 99%